Expression and functionality of TRPV1 receptor in human MCF‐7 and canine CF.41 cells. (19th March 2013) - Vercelli, C.; Barbero, R.; Cuniberti, B.; Odore, R.; Re, G.
Abstract As canine mammary tumours (CMT) and human breast cancer share clinical and prognostic features, the former have been proposed as a model to study carcinogenesis and improved therapeutic treatment in human breast cancer. In recent years, it has been shown that transient receptor potential vanilloid 1 (TRPV1) is expressed in different neoplastic tissues and its activation has been associated with regulation of cancer growth and progression. The aim of the present research was to demonstrate the presence of TRPV1 in human and canine mammary cancer cells, MCF‐7 and CF.41, respectively, and to study the role of TRPV1 in regulating cell proliferation. The images obtained by Western blot showed a signal at 100 kDa corresponding to the molecular weight of TRPV1 receptor. All tested TRPV1 agonists and antagonists caused a significant decrease (P < 0.05) of cell growth rate in MCF‐7 cells. By contrast, in CF.41 cells capsaicin and capsazepine induced a significant increase (P < 0.05) in cell proliferation, whereas resiniferatoxin (RTX) and 5‐iodo‐resiniferatoxin (5‐I‐RTX) had no influence on CF.41 cell proliferation. Further studies are needed to elucidate the underlying molecular mechanism responsible for the different effects evoked by TRPV1 activation in MCF‐7 and CF.41 cells.